Topoisomerase Sequences of Coagulase-Negative Staphylococcal Isolates Resistant to Ciprofloxacin or Trovafloxacin - Dubin, Donald T. (American Society for Microbiology, 1999)
Coagulase-negative staphylococcal isolates (n = 188) were screened for susceptibility to oxacillin, ciprofloxacin, and trovafloxacin, a new fluoroquinolone. At an oxacillin concentration of ≥4 μg/ml, 43% were methicillin resistant; of these, 70% were ciprofloxacin resistant (MIC, ≥4 μg/ml). Of the methicillin-resistant, ciprofloxacin-resistant isolates, 46% were susceptible to ≤2 μg of trovafloxacin per ml and 32% were susceptible to ≤1 μg of trovafloxacin per ml. Sixteen isolates, including twelve that expressed fluoroquinolone resistance, were chosen for detailed analysis. Identification of species by rRNA sequencing revealed a preponderance of Staphylococcus haemolyticus and S. hominis among fluoroquinolone-resistant strains. Segments of genes (gyrA and grlA) encoding DNA gyrase and DNA topoisomerase IV were sequenced. Considerable interspecies variation was noted, mainly involving noncoding nucleotide changes. Intraspecies variation consisted of coding changes associated with fluoroquinolone resistance. As for S. aureus, ciprofloxacin resistance (MIC, ≥8 μg/ml) and increased trovafloxacin MICs (0.25 to 2 μg/ml) could be conferred by the combined presence of single mutations in each gyrA and grlA gene. Trovafloxacin MICs of ≥8 μg/ml also occurred, but these required an additional mutation in grlA.